1996
DOI: 10.1002/jhet.5570330356
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti‐HIV‐1 activity of 1,5‐dialkyl‐6‐(arylselenenyl)uracils and ‐2‐thiouracils

Abstract: The 1,5‐dialkyl‐6‐(arylselenenyl)uracils 10a‐h and ‐2‐thiouracils 10i‐p have been synthesized as potential anti‐HIV‐1 agents. Cyclization of N‐alkyl‐N'‐[3,3‐di(methylthio)‐2‐alkylacryloyl]ureas 6a‐d and ‐thioureas 6e‐h in acetic acid either containing a catalytic amount of methanesulfonic acid at 80°or containing 1 equivalent of methanesulfonic acid at room temperature afforded 1,5‐dialkyl‐6‐(methylthio)uracils 7a‐d in 84–96% yields and 1,5‐dialkyl‐5,6‐dihydro‐6,6‐di(methylthio)‐2‐thiouracils 11a‐d in 88–99% y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The 6-((3,5-dimethylphenyl)thio) derivative 18 was the most inhibitory to HIV-1 replication with an EC 50 value of 0.064 µM and a selectivity index (SI, ratio of 50% cytotoxic concentration (CC 50 ) to EC 50 ) of 516. However, modification at the 2-or 4-position of the C-6-(phenylthio) ring with a methyl group diminished, or destroyed, the anti-HIV-1 activity; the 6-((2-methylphenyl)thio) derivative 15 was found to be moderately active, and the 6-((4-methylphenyl)thio) Since it has been confirmed that the two methyl groups at the 3-and 5-positions of the C-6-(phenylthio) ring contributed to the maximum activity in these 1-alkoxy-5isopropyl-6-(arylthio)uracils 14-25 as shown previously in the HEPT analogs, [22][23][24][25] we selected a ((3,5-dimethylphenyl)thio) group as the C-6 substituent for the following target compounds 26-49.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…The 6-((3,5-dimethylphenyl)thio) derivative 18 was the most inhibitory to HIV-1 replication with an EC 50 value of 0.064 µM and a selectivity index (SI, ratio of 50% cytotoxic concentration (CC 50 ) to EC 50 ) of 516. However, modification at the 2-or 4-position of the C-6-(phenylthio) ring with a methyl group diminished, or destroyed, the anti-HIV-1 activity; the 6-((2-methylphenyl)thio) derivative 15 was found to be moderately active, and the 6-((4-methylphenyl)thio) Since it has been confirmed that the two methyl groups at the 3-and 5-positions of the C-6-(phenylthio) ring contributed to the maximum activity in these 1-alkoxy-5isopropyl-6-(arylthio)uracils 14-25 as shown previously in the HEPT analogs, [22][23][24][25] we selected a ((3,5-dimethylphenyl)thio) group as the C-6 substituent for the following target compounds 26-49.…”
Section: Resultssupporting
confidence: 65%
“…Overall, structure-activity relationships in these 1-alkoxy-5-alkyl-6-(arylthio)uracils are in good agreement with those established in HEPT analogs. 20,[22][23][24][25] When the anti-HIV-1 activity of the most potent compound 18 was compared with that of AZT, DDC, DDI, and HEPT, 18 was 14-fold less potent than AZT, but 3-, 44-, and 130-fold more potent than DDC, DDI, and HEPT, respectively. The inhibitory effect of compound 18 on the replication of HIV-1 (HTLV-III B ) in human peripheral blood mononuclear cells (PBMCs) was evaluated as previously described, 10,17 and the results are shown in Table 5 along with that of AZT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 The alkylation at C-6 using lithiation is dependent on the substituent at N-1, and derivatives with N-1 alkoxy substituents could not be lithiated at C-6. 50,51 The position of the oxygen in the ethoxymethyl substituent at N-1 of the HEPT analogues may thus stabilize the 6-lithiated intermediates. Analogues with different substituents at N-1 have been made by removing the N-1 ethoxymethyl substituent, followed by benzylation at N-3, alkylation at N-1, and finally removal of the N-3 benzyl protection.…”
Section: Synthesis Of Heptmentioning
confidence: 99%